Diagnostic whole exome sequencing in presumably autosomal recessive inherited retinal dystrophies in an Iranian population - Pam A.T. Heutinck; Adriana I. Iglesias; Dariush D. Farhud; Marianne van Tienhoven; Atiyeh Khoshraftar; Marjan Zarif-Yeganeh; Sima Kheradmand Kia; Mohsen Ghanbari; Magda A. Smoor; Caroline C.W. Klaver; Lies H. Hoefsloot; Alberta A.H.J. Thiadens; et al. (Scientific Reports)
Abstract Advances in genetic testing have improved IRD diagnostics and counseling. To enhance these advances and contribute to an inclusive genetic landscape, this study examines genetic causes in 111 Iranian patients clinically diagnosed with non-syndromic IRD (48% males, > 90% born to consanguineous parents, median age at genetic examination of 37 years (interquartile range 30–42)). Patients were analyzed by ethnicity. Whole exome sequencing using a vision disorder gene panel, including copy number variations analysis, was performed at Erasmus MC. Variants were classified per American College of Medical Genetics and Genomics guidelines, with clinical significance assessed via public databases. Genetic causes were identified in 66 patients (59%) across 31 genes, including 14 novel variants. Five patients were diagnosed with syndromic IRD based on genetic findings. Homozygous variants, indicating autosomal recessive (AR) inheritance, were detected in 62 patients (94%). The most affected genes were CERKL (n = 8), EYS (n = 7), and RPE65 (n = 6), with CERKL most common in Turks (n = 6), RPE65 in Kurds (n = 4), and EYS in Fars (n = 3). Variants of uncertain significance were identified in 35 patients (32%). This study identified 14 novel variants and a high prevalence of AR inheritance, underscoring the necessity of tailored genetic counseling and the importance of incorporating diverse populations into genetic research.